Recognizing products of palaeoclimate fluctuation in the fluvial stratigraphic record: An example from the Pennsylvanian to Lower Permian of Cape Breton Island, Nova Scotia. Issue 5 (17th March 2014) - Allen, Jonathan P.; Fielding, Christopher R.; Gibling, Martin R.; Rygel, Michael C.
Abstract Tectonics and climate are the major extrinsic upstream controls on both the external and internal architectures of fluvial channels. While the role of tectonics has been well‐documented, the role of climate has received less attention. Because both tectonics and climate can produce similar stratigraphic architectures, the ability to recognize and differentiate these has major ramifications for the interpretation of fluvial stratigraphy. The Pennsylvanian to Permian succession of the Maritimes Basin complex on Cape Breton Island is ca 5 km thick, and is composed of predominantly non‐marine strata deposited within a series of depocentres characterized by different subsidence regimes. Basins in the west are transtensional depocentres characterized by episodic fault movement. In contrast, basins in the east were formed during prolonged periods of passive thermal subsidence. The stratigraphy is composed of four second‐order sequences (A to D), each 5 to 10 Myr in duration. These sequences are composed of amalgamated fluvial channel deposits that fine upwards into extensive mud‐dominated floodplain deposits with isolated fluvial channel bodies. A spectrum of fluvial styles is recorded within the study area including perennial, perennial/intermittent and ephemeral. Four stratigraphic intervals (E1 to E4) are recognized in which the deposits of strongly seasonal perennial/intermittent fluvial deposits are predominant. These intervals, 2 to 6 Myr in duration, are correlated across the study area between basins with differing tectonic regimes and do not correlate with a particular position in second‐order sequences. This suggests that climate exerted the dominant influence on the formation of these intervals and can be differentiated from tectonic imprints. While the tectonic regime of a particular basin exerted a fundamental control on the external architecture, a coherent record of climate change is recognized in the internal architecture of fluvial units. This study demonstrates that tectonic and climatic controls can be recognized and differentiated in vertical successions by evaluating the changes in fluvial architecture.